O‘ZBEKISTONDA NOMODDIY MADANIY MEROS MUHOFAZASI (Scientific journal of the Fergana State University, 2024)
This article analyzes the attitude towards intangible cultural heritage and the work being carried out to preserve and popularize it in the Republic of Uzbekistan. In particular, the elements included and planned for inclusion in the UNESCO list of intangible cultural heritage are highlighted, as well as issues of further development of their protection, scientific study and popularization.